Dry-fog disinfection as a method for processing vehicles for passenger transport - Buhl Sebastian; Stich Alexander; Bulitta Clemens (Current Directions in Biomedical Engineering, 2022)
Due to the corona pandemic, the demand for efficient and fast-acting disinfection measures is high. In this work, the disinfecting potential of a dry fogging technology (Apollon Biotech GmbH, Germany) was investigated for the possibility of disinfection of vehicles for passenger transport. This could represent a new approach for processing emergency vehicles or local passenger transport vehicles quickly and cost-effectively. A public bus was used as a model for a passenger transport vehicle (Ferienfahrschule Hense GbR, Germany). This vehicle was tested at predetermined points before and after dry-fog disinfection with swab and contact plate samples. In addition, contaminated sample tiles (Staphylococcus aureus ATCC 6538; 5x104 CFU) were placed at some locations in order to be able to record a standardized germ reduction. To determine the decontamination effect of the air in the vehicle, active airborne germ measurements were performed. In the airborne germ measurement, our results indicated a reduction of approx. 68% of the microbiological air contamination. Screening of the total contamination of the bus at several selected sites showed an average load of approximately 348 CFU per test site. After disinfection, the average bacterial count was reduced to approx. 18 CFU per test site. This disinfecting effect could also be shown with the standardized test tiles. An efficiency level of between log 0.8 and 3.7 was obtained at the various test sites.